Orangutans Are Awesome ! - Allan Morey (Raintree, 2016)
Swing! Orangutans move from branch to branch, looking for fruit to eat. These giant apes are the largest animals living in the trees of the rain forest. Engaging text, bold photos, and colorful maps shine a spotlight on these big apes. Readers are introduced to physical features, behavior, habitat, and life cycle to find out why orangutans are awesome!
Keywords: Easy Read Nonfiction -- Easy Read Nonfiction